Family Business Interests under the Matrimonial Property and Companies Legislation An Introduction - Grainer, Virginia; Dugan, Bob (Victoria University of Wellington Law Review, 1999)
This article is a preliminary investigation of family business interests under the Matrimonial Property Act 1976 ('MPA') and the Companies Act 1993 ('CA'). This article introduces the reader to the interrelationship of the matrimonial property regime and the legislative regulation of business entities, focusing on the implications of the MPA for the choice of entity, source of finance, division of shares, and allocation of management responsibility. Two principal lessons emerge from the authors' analysis: first, as applied to family ventures, the business entities legislation provides extensive flexibility with its ample allowance for contractual autonomy; and secondly, the matrimonial property regime is unsuitable for family structures involving a business operation. The authors conclude that the current regime for unmarried separate property, accessible by a MPA agreement under s 21, operates in a far more predictable manner and better suits the interests of many spouses.